Um estudo de caso do letramento literário em famílias de camadas populares - Virginia de Souza Avila Oliveira (2015)
Developed in the scope of Education and Language, this thesis connects the theoretical contributions of the New Literacy Studies (HEATH,1983; STREET, 1984) and the contributions arising from the studies of the Literary Literacy ( COSSON, 2006; PAULINO, 2009), recently developed in Brazil to examine the meaning of literary reading and writing in the lower classes. In order to achieve the primary objective of the research, it was performed a study of an ethnographic nature (GREEN; BLOOME, 1982) with the lower classes families residing in Morro do Papagaio; its name fictionally attributed. This is located in Nossa Senhora da Penha Avenue, in Belo Horizonte, Minas Gerais. From these contributions, the concepts of events of literacy (STREET, 2012), practice of literacy (STREET, 2012), and literary literacy (COSSON, 2006) became fundamental to the construction, analysis and interpretation of the data presented throughout this thesis. Three research subjects have been selected: Luzia, 32 years old, Tatiana, 10 years old, and Matheus, 15 years old. The first one assigns the responsibility for her insertion and permanency in literary writing to her schooling, institutions and religious projects. The second one; however, has had frequent contact with literature due to her familys investments in such matter, to the incentive of a formal school and to the broadening of her literary experience in Casa do Beco, institution located within Morro do Papagaio. Lastly, the third subject has a family that despite showing behaviors that reinforce Matheus needs to join the work force from a young age, offered him aid along with his formal schooling, in the incursions of the writing Universe. Furthermore, the creation and updates of his blog allowed him to make the most diverse experiments with the literary art. The final notes of the thesis concluded that during the description, analysis and interpretations of data of this work, the concept of literary literacy (COSSON, 2006) was adopted in an inclusive perspective, in a way to recognize the voice of literature outside the academic context. Thus, it was concluded each subject has their own way to denote literature in their daily lives, and each is influenced by their personal family dynamics and by instances of reading and writing fomentation present at Morro do Papagaio and at their academic trajectory.